Do HDR displays support LDR content?: a psychophysical evaluation - Akyüz, Ahmet Oǧuz; Fleming, Roland; Riecke, Bernhard E.; Reinhard, Erik; Bülthoff, Heinrich H (ACM Transactions on Graphics (TOG), 2007)
The development of high dynamic range (HDR) imagery has brought us to the verge of arguably the largest change in image display technologies since the transition from black-and-white to color television. Novel capture and display hardware will soon enable consumers to enjoy the HDR experience in their own homes. The question remains, however, of what to do with existing images and movies, which are intrinsically low dynamic range (LDR). Can this enormous volume of legacy content also be displayed effectively on HDR displays? We have carried out a series of rigorous psychophysical investigations to determine how LDR images are best displayed on a state-of-the-art HDR monitor, and to identify which stages of the HDR imaging pipeline are perceptually most critical. Our main findings are: (1) As expected, HDR displays outperform LDR ones. (2) Surprisingly, HDR images that are tone-mapped for display on standard monitors are often no better than the best single LDR exposure from a bracketed sequence. (3) Most importantly of all, LDR data does not necessarily require sophisticated treatment to produce a compelling HDR experience. Simply boosting the range of an LDR image linearly to fit the HDR display can equal or even surpass the appearance of a true HDR image. Thus the potentially tricky process of inverse tone mapping can be largely circumvented.
Keywords: Psychophysics; Riecke; Riecke_2007; bernhard-riecke; display algorithms; high dynamic range display devices; high dynamic range imaging; human information processing; iSpaceWeb; image displays; journalPaper; tone mapping